2016
DOI: 10.1177/1747954116655050
|View full text |Cite
|
Sign up to set email alerts
|

The within-task criterion to determine successful and unsuccessful table tennis players

Abstract: The aim of this study was to examine the differences in visual search behaviour between a group of expert-level and one of novice table tennis players, to determine the temporal and spatial aspects of gaze orientation associated with correct responses. Expert players were classified as successful or unsuccessful depending on their performance in a video-based test of anticipation skill involving two kinds of stroke techniques: forehand top spin and backhand drive. Eye movements were recorded binocularly with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Ward and Williams 11 found that players between 9 and 13 years of age are more likely to use task-irrelevant information when compared with U-15 and U-17 players. Our findings suggest that although of "space" looks to be the most important source of information in this task and also a visual pivot, spend too much time looking it might impairs player's decision making, as a cost benefit between "reading" the game and acting 20,26 , because the older categories used this information less frequently. Additionally, an alternative explanation is related to the film task, which was used in an aerial perspective in our study.…”
Section: Discussionmentioning
confidence: 80%
“…Ward and Williams 11 found that players between 9 and 13 years of age are more likely to use task-irrelevant information when compared with U-15 and U-17 players. Our findings suggest that although of "space" looks to be the most important source of information in this task and also a visual pivot, spend too much time looking it might impairs player's decision making, as a cost benefit between "reading" the game and acting 20,26 , because the older categories used this information less frequently. Additionally, an alternative explanation is related to the film task, which was used in an aerial perspective in our study.…”
Section: Discussionmentioning
confidence: 80%
“…The quantitative and quality of skill assessments tapped into a range of table tennis skills to measure change in participant’s abilities, but they did not assess all table tennis shots (e.g. drive, flick, smash) and were not based on objective measures such as video-based movement trajectory [17] or eye movement measurements [26]. In addition, we could not compare the effectiveness of VR sports training compared to real-world training because our study did not include a real-world training group.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific literature devotes a lot of attention to professional table tennis, in particular, to features affecting players’ performance or talent [ 15 , 16 , 17 , 30 , 46 , 47 , 48 , 49 ], while articles devoted to the socio-economic determinants of recreational practice are rather scarce [ 38 , 39 , 40 ]. Except for StrawiƄski [ 38 ], Polish literature focuses on the historical development of the discipline and its contribution to society [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that regular training can help maintain mental capacity and prevent or delay senile dementia [ 26 ] and (by moulding motor skills social behaviour) can be a great therapeutic agent for children with attention deficit hyperactivity disorder (ADHD) [ 27 ], autism [ 28 ] and mild mental disabilities [ 29 ]. Since table tennis is numbered among one of the fastest ball games in the world [ 13 , 15 ], a major part of studies have focused on strategies of visual search [ 30 ]. Other studies have shown that table tennis can also improve the dynamic visual acuity (DVA) of the general population [ 31 ], the biomotor capacities of children in general [ 32 ] and static balance of deaf children [ 33 ].…”
Section: Introductionmentioning
confidence: 99%